The Islamic Musical Sciences and the Andalusian Connection: Juan Andrés’ «Letter on Arabic Music» (1785) - Donoso , Isaac Donoso (Jurnal Usuluddin, 2021)
Music was an essential part of the philosophical knowledge in the classical antiquity and then in the medieval era. Music provided tools to foster a global speculative knowledge, and the classical Islamic thought developed different musical sciences. This paper tries to describe the different approaches to the musical phenomenon from an Islamic perspective, and the feasible transmission of this knowledge to Western music via al-Andalus. In doing so, the paper places attention in the Italian «Letter on Arabic Music» written by the Spanish Jesuit Juan Andrés in 1785, one of the first documents attesting this connection.